(untitled) (Global Scientific Review, 2025)
Obesity is a chronic disease of the 21st century and a global epidemic [1]. According to statistics, 1.4 billion adults worldwide are overweight [2, 3]. Of these, 900 million women and over 500 million men suffer from obesity. Morbid obesity is defined as excessive fat deposition with a body mass index (BMI) ≥ 40 kg/m² or BMI ≥ 35 kg/m² in the presence of obesity-related metabolic syndrome [3]. Twelve million adults in the United States suffer from morbid obesity with a BMI ≥ 40 kg/m² [4]. In Russia, according to the World Health Organization (WHO) in 2018, 23.5 million people were registered as obese [5]. According to WHO data, the average BMI in Uzbekistan is currently 26.5 kg/m², the highest in Central Asia [6]. Studies by Halliday T.A. and Sundqvist J. have shown that diets and weight-loss medications are ineffective in patients with morbid obesity [7, 8, 9]. Bariatric surgery has been proven to be the most effective long-term intervention for weight loss in obese patients [10, 11, 12]. Bariatric surgery is considered a treatment option for class III obesity (BMI ≥ 40 kg/m²) or class II obesity (BMI 35.0–39.9 kg/m²) with obesity-related comorbidities that have not responded to conservative treatment and other methods [13].